Coconstruire un outil d’aide à la décision : le manuel paysager et environnemental de la gestion forestière pour le Parc naturel régional de la Sainte-Baume - Atelier Saltus; Nicolas Luigi (Projets de Paysage)
This article presents an experimental working method which was born from the combined perspectives of the landscape designers of the Saltus workshop, who are specialists of the Mediterranean climate, and two forestry engineers from the Avisilva design office. The forest is a major feature of the region of Sainte Baume, because of the surface area it occupies and of the economic, ecological, environmental, and social functions it fulfils. Aware of the impact of forest development, over time local communities have adopted ambitious forestry policies. A management tool for the preservation of the forest landscapes and biodiversity of the Regional Nature Park was needed to implement local policies for the preservation of the region’s nature areas. A cross between a decision-making tool and a planning tool, this handbook in landscape and environmental management is intended to be a transverse document. It reconciles scientific and technical approaches to fulfil educational and operational objectives. This landscape project, the scope of which ranges from the individual plot to the entire region, is principally based on the disciplines of geography (geomorphology, hydrology, anthropology) and ecology (plant series, climatology, biodiversity), and is intended to develop a dynamic vision of the forest ecosystems of the region. It combines theoretical work and field work, examines the relevance of scale when addressing landscape and environmental issues in the management of forest areas, and calls for the creation of new representation tools.